2022
DOI: 10.3389/fmicb.2022.811755
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Ecological Diversity of Escherichia coli and Cryptic Escherichia Clades in Subtropical Aquatic Environments

Abstract: Escherichia coli not only inhabit the large intestines of human and warm-blooded animals but could also persist in the external environment. However, current knowledge was largely based on host-associated strains. Moreover, cryptic Escherichia clades that were often misidentified as E. coli by conventional diagnostic methods were discovered. Failure to distinguish them from E. coli sensu stricto could lead to inaccurate conclusions about the population genetics of E. coli. Based on seven housekeeping genes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…E. coli is a widely studied Gram-negative bacterium that plays a crucial role in various ecological niches and has significant implications for human health. Previous studies have demonstrated the presence of extensive genetic variation within E. coli , enhanced by its ability to adapt to a range of diverse niches including hospitals, animal reservoirs, and natural ecosystems (Blount 2015; Jang et al 2017; Koh et al 2022). In the clinical setting, E. coli represents a significant public health concern due to its ability to cause a wide range of infections, ranging from urinary tract infections to more severe bloodstream infections.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli is a widely studied Gram-negative bacterium that plays a crucial role in various ecological niches and has significant implications for human health. Previous studies have demonstrated the presence of extensive genetic variation within E. coli , enhanced by its ability to adapt to a range of diverse niches including hospitals, animal reservoirs, and natural ecosystems (Blount 2015; Jang et al 2017; Koh et al 2022). In the clinical setting, E. coli represents a significant public health concern due to its ability to cause a wide range of infections, ranging from urinary tract infections to more severe bloodstream infections.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, the realization that E. coli may also persist in water, soil and sediment has provided new impetus to investigate the maintenance and survival of newly described environmental E. coli ‐like Escherichia spp. (Gilroy et al, 2021 ; Liu et al, 2015 ; van der Putten et al, 2021 ), isolated from terrestrial and aquatic habitats (Koh et al, 2022 ; Mire et al, 2022 ; Moinet et al, 2024 ). The advances in molecular methods to subtype E. coli and identify E. marmotae and E. ruysiae should allow new insights into their overall abundance and association with enteric pathogen species.…”
Section: Discussionmentioning
confidence: 99%